Cyclin dependent kinase 1 (CDK1) positively regulates cardiac hypertrophy and fibrosis via TGF-beta pathway. (25th November 2020) - Yamamoto, T; Matsushima, S; Okabe, K; Ikeda, S; Ishikita, A; Enzan, N; Sada, M; Tsutsui, Y; Miyake, R; Tsutsui, H
Abstract: Background: Transforming growth factor beta (TGF-β) critically mediates cardiac fibrosis by transforming fibroblasts to myofibroblasts in pathological conditions. Cyclin dependent kinases (CDKs), cell cycle-regulating proteins, are known to be intimately involved in cardiac fibrosis. Among CDK isoforms, CDK1 is essential for cell cycle progression and cell division. It is reported some interphase CDKs such as CDK4 or CDK6 were involved in cardiac fibrosis, however, detailed mechanisms of cardiac fibrosis through CDK1 and its interactions with TGF-β in cardiac fibrotic process haven't been elucidated. We hypothesize that CDK1 is involved in cardiac fibrotic process via TGF-β pathway and its suppression decreases TGF-β expression and transformation to myofibroblasts from fibroblasts presenting antifibrotic effect. Methods and results: Isolated neonatal rat cardiac fibroblasts were treated with angiotensin II (ANG II, 1 μM, 24 h) or phosphate-buffered saline (PBS). ANG II increased CDK1 and TGF-β in cardiac fibroblasts, by 97% and 292%, respectively (p<0.05). Administration of Ro-3306, a specific CDK1 inhibitor (1 μM, 24 h), suppressed TGF-β protein levels in ANG II-treated cardiac fibroblasts by 58% (p<0.05). Similarly, knockdown of CDK1 by RNA silencing also inhibited ANG II-induced increases in TGF-β in cardiac fibroblasts by 39% (p<0.05). ANG II increased alpha-smooth muscle actin (α-SMA), which is a marker of myofibroblasts, and knockdown of CDK1 significantly suppressed it by 49% (p<0.05). In vivo study, 11-week-old male C57BL/6J mice were administered ANG II continuously with infusion pump, at a dose of 1000 ng/kg/min, for a week. Also, Ro-3306 was intraperitoneally injected at a dose of 2 mg/kg/day, every other day, for a week. First, Ro-3306 attenuated ANG II-mediated cardiac hypertrophy indicated by heart weight and echocardiographic parameter as to left ventricular wall thickness. Second, CDK1 and TGF-β expression were significantly augmented in ANG II-infused mice by 404% and 113%, respectively (p<0.05). Injection of Ro-3306 suppressed TGF-β protein levels by 48%, although the difference wasn't statistically significant (p=0.09). Finally, histopathological examination (Masson's trichrome stain) demonstrated remarkable repression of ANG II-induced cardiac fibrosis by Ro-3306. Conclusions: CDK1 positively controls cardiac fibrotic process by regulating transformation to cardiac myofibroblasts from fibroblasts via TGF-β pathway. It also presents an antihypertrophic effect on ANG II stimulation. CDK1 is a potential therapeutic target of cardiac fibrosis and hypertrophy. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): KAKENHI